The impact of virtual social networks on political consumerism - محمودرضا رهبرقاضی; Marzye Fadaee Dah Cheshmeh; Azam Shahriari (مطالعات رسانه‌های نوین, 2017)
The aim of this study was to evaluate the impact of various aspects of social networking (duration of membership in social networks, the daily use of social networks, the user's activity on social networks, and the true extent deemed a social network content from a user perspective) on political consumerism. In other words, any social-network activity level in more depth will, in favor of political consumerism also increases. The statistical population of this research includes all university students in Isfahan city in the academic year of 2011-2012. By cluster sampling, 327 of them were selected as sample size and studied by scrolling method. In this regard, the results of the research show that only the amount of activity in social networks has a significant effect on political consumption. In other words, the level of activity of people in social networks is deeper, their tendency to political consumption also increases. .